2023
DOI: 10.3389/fimmu.2023.1161479
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related proteomics demonstrate landscape of fracture blister fluid in patients with acute compartment syndrome

Abstract: BackgroundBlisters are tense vesicles or bullae that arise on swollen skin and are found in a wide range of injuries. As a complication of fracture, fracture blisters are considered soft tissue injuries, which often lead to adverse effects such as prolonged preoperative waiting time and increased risk of surgical site infection. However, our previous study found that in patients with acute compartment syndrome, fracture blisters may be a form of compartment pressure release, but the specific mechanism has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In our previous research, complete blood counts revealed that the levels of NEU and CKMB were related to ACS, but a limited number of inflammation-related indicators were observed. Our recent studies also found some variations of inflammatory cytokines in patients with fracture blister fluid and plasma through Olink Proteomics analysis (11,12). Therefore, we used the inflammatory panel of Olink Proteomics analysis to identify the biomarkers of ACS in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous research, complete blood counts revealed that the levels of NEU and CKMB were related to ACS, but a limited number of inflammation-related indicators were observed. Our recent studies also found some variations of inflammatory cytokines in patients with fracture blister fluid and plasma through Olink Proteomics analysis (11,12). Therefore, we used the inflammatory panel of Olink Proteomics analysis to identify the biomarkers of ACS in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Vitreous samples were measured using the Olink ® INFLAMMATION panel* (Olink Proteomics AB, Uppsala, Sweden) according to the manufacturer’s instructions, which allows the simultaneous analysis of 92 analytes using 1 µL of each sample ( 13 , 14 , 16 ). Detailed information about the panel can be found in the Supplementary files , Supplementary Data Sheet 1 .…”
Section: Methodsmentioning
confidence: 99%